Molecular evidence for the involvement of alternative splicing in jejunum epithelial cells in broiler chickens fed dietary supplementation with olive mill wastewater: Alternative splicing in broiler chickens - Bebane, Pshtiwan; Mustafa, Sarbast Ihsan; Taha, Hevidar; Darweesh, Omeed; Kheder, Ramiar K. (Cellular and Molecular Biology, 2023)
There is no doubt that alternative splicing is conserved in chickens and mammals, but evaluating the effects of nutrition on alternative splicing in chickens is crucial in a wide range of fields. Although the olive diet has been extensively studied in human, mouse, and chicken systems, little is known about its impact on chicken alternative splicing systems. Hence, the current study aimed to assess the effect of feeding polyphenol-enriched olive mill wastewater to female broiler chickens via alternative splicing by analyzing high-throughput sequencing raw reads of RNA utilizing genomics and bioinformatics methodologies. It also aimed to look for differences in isoform expression and discover molecular functions and biological processes linked to differentially transcribed genes. The findings of our study revealed that 51 genes involved in isoform switching and alternative splicing events were not used evenly. This is due to the reduced use of ATSS in olive mill wastewater groups compared to control groups. Furthermore, the gene ontology analysis revealed that 25 GO terms were enriched in biological processes, 16 GO terms were enriched in molecular function, and 25 GO terms were enriched in cellular components. Kinase and adenylyltransferase activities were significantly enriched in terms. The molecular analysis presented herein provides valuable insight into the role of phenolics in alternative gene-splicing mechanisms in chickens, demonstrating how an industrial waste product can be repurposed as a feed supplement with a satisfactory outcome.